Bibliometric Analysis and Network Visualization in Credit Risk Studies: The Role of Machine Learning in Financial Risk Management - Nur Fadila; Sri Andriani (CV. ITTC INDONESIA, 2025)
This study explores the development and research trends related to credit risk through a bibliometric approach and network visualization using VOSviewer software. By analyzing internationally indexed scientific publications from 2015 to 2025, the study aims to identify major themes, topic evolution, and key contributors in the field. The results reveal a growing academic interest in credit risk, particularly in the application of advanced technologies such as machine learning for risk evaluation and management. This research not only provides a visual mapping of the evolving academic landscape but also uncovers under-researched areas. The findings offer strategic insights for future research directions and support risk-based decision-making in the modern financial sector.